الفقه الكلي مفهومه - مصادره - إعماله: دراسة فقهية مقاصدية - اللميع، فيصل أحمد (جامعة الأزهر - كلية الشريعة والقانون بالقاهرة, 2021)
يناقش هذا البحث مفهوم الفقه الكلي وإعماله؛ فإن الفقه الإسلامي يشتمل على جانب جزئي يتعلق بآحاد المسائل الفقهية، وعلى جانب كلي يتعلق بالقواعد والمعاني الكلية، والجانب الكلي من الفقه الإسلامي هو الهدف الذي تتولى هذه الدراسة تناوله من جهة مفهومه، ومصادره، وإجراءات إعماله، وأبرز مجالات إعماله مستخدما في ذلك المنهج الاستقرائي لأجل استقراء النصوص الشرعية وكلام أهل العلم في كليات الفقه الإسلامي، والمنهج التحليلي من خلال تحليل النصوص الشرعية وكلام أهل العلم في شأن كليات الفقه الإسلامي، ووضعه في سياقه المناسب. وقد مما توصلت إليه الدراسة بيان مفهوم الفقه الكلي، وأنه العلم بالثوابت الشرعية المعقولة المعنى، التي يبنى عليها ما لا حصر له من أحكام الجزئيات، كما تناولت أبرز مصادره، ومنهجية إعمال الفقه الكلي، وأبرز مجالات الإعمال. وكان مما توصلت إليه الدراسة أيضا: أن الفقه الكلي استعمله الفقهاء والأصوليون في سياقات مختلفة، وأنه الكفيل ببيان استراتيجيات الفقه الإسلامي، وما تريد الشريعة الحفاظ عليه واعتباره دائما، وأن تطبيق الفقه الكلي يسير على مقتضى منظومة تطبيقية متكاملة الأركان، يتم فيها تحديد الثابت من المتغير في الأبواب الفقهية، والمقصود لذاته من المقصود لغيره، وعرف التشريع في الأبواب الفقهية المختلفة، كما يوضح القواعد والضوابط، والأصول العامة للفقه الإسلامي، ويراعي حاجات الناس، واختلاف الأحوال، ويفرق بين أوقات الضرورة وأوقات الاختيار، ويربط الجزئي بكليه.
This paper discusses the concept of comprehensive Islamic jurisprudence and its factual application. Islamic jurisprudence can be divided into a very detailed sub-aspect related to individual jurisprudential issues, and a comprehensive Islamic jurisprudence aspect related to main principles and overall concepts. That comprehensive Islamic jurisprudence is the main purpose of this study which meant to address its definition, its sources, and the tools of its performance, and the most prominent aspects of its performance using that inductive approach along with the analytical approach on analyzing Shariah divine texts and Shariah scholar’s jurisprudence in the comprehensive Islamic jurisprudence and to classify it in its appropriate context. The study concluded to a certain definition of the concept of comprehensive Islamic jurisprudence which is the comprehension of the accepted and unchangeable Shariah rules which constitute the basis for many other detailed rulings. The study also addressed Fiqh Maqāṣidia most prominent sources, the mechanism of its application, and the most familiar cases of its application. The study also concluded that comprehensive Islamic jurisprudence has been in use from Islamic jurisprudence jurists in different contexts, further, that science is suitable to define the strategy, and what Shariah law really seeks to observe and last. In addition, the application of comprehensive Islamic jurisprudence is bond by fully applicable specific Islamic jurisprudence in which differentiate between the sustained from inconstant in Islamic jurisprudence chapters, and what is self-meant from what is meant for another, the custom of legislation in every chapter of Islamic jurisprudence, the standers and regulations, the general principles of Islamic jurisprudence, human needs, different circumstances, and defernite between the circumstances of necessity and comfort and to relate the secondary ruling by the comprehensive one.
Keywords: التشريع الإسلامي -- المقاصد الإسلامية -- الفقه الإسلامي -- الفقه الكلي